The Canadian Chronic Disease Surveillance System: A model for collaborative surveillance. (2018) - Lix, Lisa; Ayles, James; Bartholomew, Sharon; Cooke, Charmaine; Ellison, Joellyn; Emond, Valerie; Hamm, Naomi; Hannah, Heather; Jean, Sonia; LeBlanc, Shannon; Paterson, J. Michael; Pelletier, Catherine; et al.
No abstract available